Dare to win / by Jack Canfield and Mark Victor Hansen - "Canfield, Jack" (Bhopal, 2012)
Jack Canfield and Mark Victor Hansen have inspired millions of people around the world to break through their fears and create their ideal lives. Now, in Dare to Win, they show you how to eliminate the roadblocks that prevent you from fulfilling your potential so you can get what you want out of life. Dare to Win teaches you to think like a winner you truly are and to believe in what you can become.
Keywords: Self improvement